Grundtvigs folkelighedsbegreb - Andersen, Balder Mørk (Grundtvig-Studier, 2003)
Grundtvigs folkelighedsbegreb [Grundtvig’s Concept of ’Folkelighed’] By Balder Mork Andersen With Grundtvig’s own writings underpinning a dialogue with previous commentators, the article seeks to clarify elements in, and the significance of, Grundtvig’s concept offolkelighed. This then makes possible an assessment of the compass and the spectrum within which his thinking on nationhood developed. The principal method here has been to take as a point of departure the degree of influence exerted by the German philosophers Herder and Hegel who had earlier nurtured ideas concerning folk and fatherland. Analysis of the concept of folkelighed is made against the background of a survey of three separate, yet at the same time linked, chief components in Grundtvig’s conceptual world: folkeand, fadreland and modersmal [‘folk-spirit’, ‘fatherland’, ‘mother-tongue’]. Folkeand is perceived as the basic understanding of an idea of communality which must be constantly alive and alert in heart and in mind. Grundtvig requires that the folk opens itself up and embrace communality, though in such a way as not to curtail individuality. In the modersmal, the folkeand finds the optimum means of manifesting itself. For Grundtvig, the national and native language is the embodiment, tool and articulation of the folkeand, and without it no nation can flourish. At the same time, a feeling for the mother-tongue is for Grundtvig a crucial precondition for being Danish. On this point Grundtvig displays throughout his adult life a consistency of thinking in contrast to most other areas where his self-critical revaluations make it difficult to view him as a systematic thinker. The evolution of his thinking about the fadreland was somewhat characterised by changeability, in tandem with historical developments in the country. However, it is certainly the case that for Grundtvig love of the fadreland was a basis for the love of God and therefore that which legitimised cultivation of nationalism. He was fully aware that a selfsacrificing love of the fadreland could manifest itself in ethnocentric form; but this does not prevent one from justly pointing to instances where Grundtvig himself loses this focus and allows the culture of nationalism to take on a negative expression. It is, for example, problematic when he mixes politics and religion together and uses Christianity to legitimise acts of war. This notwithstanding, the overall picture affirms that Grundtvig basically found that there was no justification for exercising spiritualintellectual violence against people of a different nationality and that physical violence could be resorted to only when the country was threatened by aggressors. Thus his nationalistic thinking is of a polycentric character and closely tied to that of J. G. Herder. All in all, folkelighed is to be seen as a spiritual-intellectual and historical communality of values where all make their contributions and nurture feelings for the state of the nation, past, present and future. When the three strains - folkeand, fadreland and modersmal – sounded together in harmony, then, for Grundtvig, there could be talk of an authentic Danish folkelighed.